The effect of spatial scale on the use of biodiversity surrogates and socio-economic criteria in systematic conservation assessments - Payet, Karine (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Conservation Ecology and Entomology)--Stellenbosch University, 2007.